Antibacterial properties of Tualang, Acacia and Yemeni Sumur honey against selected food spoilage bacteria and foodborne pathogens - Mohamed, Khadra Yousuf; Mahmud @ Ab Rashid, Nor Khaizura; Zainal Abidin, Nur Hanani; Mohammad Rashedi, Ismail Fitry (Rynnye Lyan Resources, 2021)
The antibacterial activity of honey is mainly credited to its acidity, osmolarity and enzymatic generation of hydrogen peroxide via glucose oxidase. Additional honey components, such as aromatic acids or phenolic compounds, also contribute to the overall antibacterial activity. The level of antibacterial activities found in honey varies with different types of honey, due to mainly the composition, percentage as well as the nature of the sugars present in the honey. This study aimed to evaluate the antibacterial activity of four types of honey, namely Tualang honey (TH1), Tualang honey (TH2), Acacia honey (AH) and Yemeni Sumur honey (YSH). Nine bacterial strains were used. Disc diffusion, well diffusion, minimum inhibitory concentration (MIC), Minimum bactericidal concentration (MBC), and time-kill methods were performed to reveal the antibacterial potential of the selected honey. The MIC values ranged between 12.5 to 50% for both TH1 and YSH while for TH2, and AH it ranged between 25 to 50%. For MBC, it ranged from 25 to 50%. The time-kill in TH1 Staphylococcus aureus (food isolate) showed total inhibition at 6 hrs in 2 X MIC, and for Staphylococcus aureus ATCC 29737 was 3.84 log CFU/g at the 6 hrs. Physicochemical quality of honey resulted as follows: the pH of the honey samples was acidic in nature ranging between 3.69 to 3.94, and the aw of the honey samples were between 0.53 to 0.69. For colour analysis, YSH was observed to has the maximum lightness and yellowness, and TH1 has the maximum redness. While, AH had a minimum lightness, redness, and yellowness.